FCO2: Green Infrastructure Supporting Indonesia Carbon Neutral 2060 - Tirta, Monixca Fernandes Awangga; Unas, Frisca Maria; Chandradiningrat, Nugroho Wahyu (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Climate change is often a problem in almost every country. This is inseparable from the crucial problems related to climate change issues experienced by Indonesia from year to year. One of them is the issue of increasing carbon emissions caused by various energy sectors, the automotive transportation industry, and home industries. The Climate Transparency 2021 report states that although Indonesia has proposed increasing the use of renewable energy in the fields of electricity, transportation, and industry (Climate Transparency, 2021), in addition, Indonesia does not yet have a gradual strategy related to stopping the use of coal and there is no policy that is able to encourage competition between renewable energy. and coal. Indonesia is committed to the world and targets the achievement of carbon neutrality by 2060 through the submission of the Long Term Strategy on Low Carbon and Climate Resilience 2050 document to the UNFCCC which is the mandate of the Paris Agreement which has been ratified into Law no. 16 of 2016 which contains the Ratification of the Paris Agreement To The United Nations Framework Convention On Climate Change. The method used in making this paper is a descriptive method with a quantitative approach based on literature review. Where in this method describes the consequences that occur from an increase in carbon emissions, solutions in dealing with problems caused by carbon emissions. The method used in collecting data in this proposal is secondary data, namely data sourced from library materials, both from articles and official websites such as the website of the Badan Pusat Statistik Indonesia. In order to achieve Indonesia's target of carbon neutral 2060, an infrastructure innovation called FCO2 was made which has an effectiveness of 80% in reducing carbon emissions. The carbon emission reduction system used in FCO2 is in the form of filtration, which functions to filter the air and exhaust gases from the carbon content caused by various industrial and vehicle activities. On the other hand, FCO2also has a part that will function in spraying disinfectant into the air to kill microorganisms, such as viruses, bacteria in the air. The disinfectant used uses natural ingredients, which are made from lime and betel leaf. In addition, so that the use of FCO2 can provide more optimal results, it is also necessary to support the government, private, and community sectors to play a major role in expanding green open space infrastructure evenly.